2015
DOI: 10.1021/acs.jmedchem.5b00050
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystal Structures of Escherichia coli RNA Polymerase with Switch Region Binding Inhibitors Enable Rational Design of Squaramides with an Improved Fraction Unbound to Human Plasma Protein

Abstract: Squaramides constitute a novel class of RNA polymerase inhibitors of which genetic evidence and computational modeling previously have suggested an inhibitory mechanism mediated by binding to the RNA polymerase switch region. An iterative chemistry program increased the fraction unbound to human plasma protein from below minimum detection levels, i.e. <1%, to 4~6%, while retaining biochemical potency. Since in vitro antimicrobial activity against an efflux-negative strain of Haemophilus influenzae was 4~8-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 39 publications
(131 reference statements)
1
35
0
Order By: Relevance
“…The near-atomic resolution X-ray crystal structure of E. coli RNAP was determined first as holoenzyme containing σ 70 (Murakami, 2013). X-ray crystal and cryo-electron microscopy (cryo-EM) structures of E. coli RNAP are now available in several forms such as holoenzymes containing alternative σ factors (Liu et al, 2016; Yang et al, 2015), promoter DNA complexes (Glyde et al, 2017; Zuo and Steitz, 2015), elongation complex (Kang et al, 2017), in complex with transcription factors (Bae et al, 2013; Liu et al, 2017; Molodtsov et al, 2018), and with inhibitors/antibiotics (Bae et al, 2015; Chen et al, 2017; Degen et al, 2014; Molodtsov et al, 2015; Molodtsov et al, 2013), providing details of the structure and function of E. coli RNAP transcription and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The near-atomic resolution X-ray crystal structure of E. coli RNAP was determined first as holoenzyme containing σ 70 (Murakami, 2013). X-ray crystal and cryo-electron microscopy (cryo-EM) structures of E. coli RNAP are now available in several forms such as holoenzymes containing alternative σ factors (Liu et al, 2016; Yang et al, 2015), promoter DNA complexes (Glyde et al, 2017; Zuo and Steitz, 2015), elongation complex (Kang et al, 2017), in complex with transcription factors (Bae et al, 2013; Liu et al, 2017; Molodtsov et al, 2018), and with inhibitors/antibiotics (Bae et al, 2015; Chen et al, 2017; Degen et al, 2014; Molodtsov et al, 2015; Molodtsov et al, 2013), providing details of the structure and function of E. coli RNAP transcription and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…2, circles 3, 4, and 5, respectively). Cocrystal structures of two squaramides with E. coli RNAP holoenzyme have recently been published, which showed that their major binding site was broadly similar to that of the myxopyronins within the switch 1 and 2 regions, with less substantial interaction with switch regions 3 and 4 (140). The cocrystal structures also demonstrated that the binding of squaramide compounds to RNAP pushed switch 2 into the DNA binding main channel of RNAP, which would prevent the correct positioning of the melted template DNA.…”
Section: Myxopyronin Corallopyronin Ripostatin and Squaramidesmentioning
confidence: 99%
“…Compounds like myxopyronins, corallopyronin (Mukhopadhyay et al, 2008), ripostatin (Mukhopadhyay et al, 2008; Belogurov et al, 2009), and squaramides (Buurman et al, 2012; Molodtsov et al, 2015) bind to RNAP β′ switch-2 region that controls the hinged, swinging motion of β′ clamp, which in turn is responsible for the opening and closing of the primary channel (Srivastava et al, 2011). Binding of these compounds prevents the β′ clamp from opening, stabilizes the β′ clamp/switch regions in a partly closed/fully closed conformation, and prevents template DNA from reaching the active site.…”
Section: Transcription Inhibitors That Target Rnapmentioning
confidence: 99%
“…Binding of these compounds prevents the β′ clamp from opening, stabilizes the β′ clamp/switch regions in a partly closed/fully closed conformation, and prevents template DNA from reaching the active site. In particular, squaramide, in its co-crystal structure with RNAP, is shown to displace β′ switch-2 into the DNA binding main channel of RNAP (Molodtsov et al, 2015), which would interfere with proper placement of the melted template DNA (Bae et al, 2015b). Fidaxomicin and lipiarmycin (Tupin et al, 2010; Artsimovitch et al, 2012; Morichaud et al, 2016) are structurally closely related natural compounds that also bind to the β′ switch-2 region and prevent t-strand DNA from accessing the RNAP active-site cleft.…”
Section: Transcription Inhibitors That Target Rnapmentioning
confidence: 99%
See 1 more Smart Citation